Impact of maternal hypothyroidism on human milk macronutrient content and fatty acid composition: a prospective cohort study - Alodhaybi, Shahad; Binobaed, Manal Abdulaziz; AlAnazi, Rasha Homoud; Elwehedy, Nora; Baraja, Muneera; Aljawoan, Fatimah Yousef; Tamimi, Waleed; Elamin, Lamia Mohammed; Madkhali, Azza (Frontiers in Nutrition, 2026)
BackgroundHypothyroidism can alter the serum lipid profile and the composition of human milk (HM) proteins involved in macronutrient metabolism. We investigated the association between maternal hypothyroidism and HM macronutrient content and fatty acid (FA) composition.MethodsIn this prospective cohort study conducted in Riyadh, Saudi Arabia, HM samples from mothers with hypothyroidism (n = 19) and mothers without hypothyroidism (n = 30) were compared. Eligible participants were breastfeeding mothers of term singleton infants with no history of metabolic disorders or chronic disease. Maternal demographic characteristics, anthropometrics, laboratory markers, dietary intake, and HM samples were collected 4–13 weeks postpartum. Primary outcomes were HM macronutrient content and FA composition, analyzed using the Miris HM analyzer and gas chromatography–flame ionization detection, respectively.ResultsForty-nine participants were recruited between December 12, 2023, and May 31, 2025. HM macronutrient content and total saturated, monounsaturated, polyunsaturated, and trans FAs (TFAs) did not differ between groups. Among mothers with hypothyroidism, 10 individual FA species differed significantly (eight higher and two lower), characterized by higher industrial TFAs and selected long-chain omega-3 and omega-6 species. Mothers with hypothyroidism had higher levels of docosapentaenoic acid (0.079 ± 0.024% vs. 0.063 ± 0.024%) and elaidic acid (0.286% [0.233–0.439%] vs. 0.118% [0.028–0.220%]), but lower levels of tricosanoic acid (0.00% [0.00–0.00%] vs. 0.011% [0.00–0.022%]) (all p < 0.05). They also had higher low-density lipoprotein cholesterol (3.45 [2.87–3.97] vs. 2.94 [2.35–3.32] mmol/L; p = 0.01), whereas other lipid parameters did not differ significantly.ConclusionMaternal hypothyroidism, even when treated with replacement therapy, was associated with altered HM FA composition. These changes may reflect thyroid hormone–related shifts in lipid metabolism, potentially influenced by maternal diet and adipose stores. Future longitudinal research is needed to investigate whether integrating thyroid-aware lactation support and targeted nutritional interventions can effectively modulate these effects and improve breastfeeding outcomes.